Power Subsidies : A Reality Check on Subsidizing Power for Irrigation in India - Monari, Lucio (World Bank, Washington, DC, 2012)
After almost a decade of high-level efforts to bring electricity tariffs closer to the cost of supply, India has barely made a dent in the long-standing and increasingly uneconomical practice of subsidizing power for irrigation. Progress has been slowed by concern that higher tariffs would harm farmers and thus undermine the achievements of the green revolution package-cheap power and water, new seeds and fertilizer-aimed at enabling the country to feed itself. But a new study shows that a package of rapid electricity sector reforms, including a move toward cost-covering tariffs and investments to improve the quality of power supply, would increase farmers' incomes by 40-100 percent over a six-year period.